2021
DOI: 10.1177/2156759x21998391
|View full text |Cite
|
Sign up to set email alerts
|

School Counselor Perceptions of Preparation and Importance of College and Career Readiness Counseling

Abstract: This study addresses school counselors’ perceptions of the importance of college and career readiness counseling and their preparedness to implement aspects of such counseling with students and families. Results from surveying school counselors in a large urban district serving a diverse, low-income student population indicated that school counselors did not believe they were well prepared to provide many aspects of college and career readiness counseling, although they perceived that each area was important t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 34 publications
(62 reference statements)
2
14
0
Order By: Relevance
“…The results from the present study also indicate that school counselors feel the least confident when working with data trends ranging from school-wide to school-specific; this finding is in accordance with previous studies (Novakovic et al, 2021;Young & Kaffenberger, 2018). Given the fact that the overwhelming majority of participants were trained within the past 15 years, well after the development of the ASCA National Model, we were puzzled that school counselors reported being least confident when using data to make college and career readinessrelated decisions.…”
Section: Preservice Trainingsupporting
confidence: 93%
See 3 more Smart Citations
“…The results from the present study also indicate that school counselors feel the least confident when working with data trends ranging from school-wide to school-specific; this finding is in accordance with previous studies (Novakovic et al, 2021;Young & Kaffenberger, 2018). Given the fact that the overwhelming majority of participants were trained within the past 15 years, well after the development of the ASCA National Model, we were puzzled that school counselors reported being least confident when using data to make college and career readinessrelated decisions.…”
Section: Preservice Trainingsupporting
confidence: 93%
“…Elementary school students are at a crucial stage where career beliefs, self-concepts, and aspirations are being developed (College Board, 2012; Gottfredson, 1981; Mariani et al, 2016; Pulliam & Bartek, 2018; Super, 1990). However, studies indicate that school counselors are not well prepared to deliver these services (Morgan et al, 2014; Novakovic et al, 2021) or are prevented from doing so due to high student-to-school-counselor ratios (Pham & Keenan, 2011). This is especially true in elementary schools (American School Counseling Association [ASCA], 2019a), which often have only one school counselor in the building, tasked with providing career, academic, and social/emotional interventions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that school counselors generally feel their academic training and pre-service counseling work only moderately prepared them to enter the counseling field (Bridgeland & Bruce, 2011;Goodman-Scott, 2015). Many counselors report a disconnect between the skills learned in pre-service training and those needed on the job-specifically, skills in areas like college and career readiness counseling (Gilfillan, 2017;Novakovic et al, 2021); consultation (Cholewa et al, 2020); and using data to support evidence-based decision-making (Young & Kaffenberger, 2015). This partially reflects the fact that many counselor preparation programs do not require coursework in key counseling content areas and that a third of counselor educators do not have previous work experience as school counselors (Pérusse et al, 2015).…”
Section: Counselor Preparationmentioning
confidence: 99%